Molecular‐based phylogenetic placement and revision of Micrasepalum (Spermacoceae‐Rubiaceae). Issue 6 (19th October 2021) - Nuñez Florentin, Mariela; Salas, Roberto M.; Janssens, Steven B.; Dessein, Steven; Cardoso, Domingos
Abstract: Micrasepalum is a taxonomically and phylogenetically poorly understood genus of Rubiaceae endemic to the global biodiversity hotspot of the Caribbean islands. It has traditionally been associated with species in the Spermacoce clade, but never properly evaluated in a phylogenetic context. Also, little information about seed and fruit morphology of Micrasepalum species was provided in their original descriptions and the few subsequent taxonomic treatments. We performed a molecular phylogenetic study based on nuclear (ITS, ETS) and plastid ( atpB‐rbcL, petD, rps16, trnL‐trnF ) DNA sequence data to resolve the enigmatic taxonomic identity of Micrasepalum . Our analyses show a largely unresolved or poorly supported backbone in both the nuclear and plastid phylogenies of the Spermacoce clade, so that the sister relationship of Micrasepalum is still uncertain. Merging Micrasepalum with any lineage of the polyphyletic Borreria and Spermacoce or the phylogenetically well‐defined Hexasepalum, Mitracarpus or Richardia would result in a morphologically heterogeneous collection of genera difficult to recognize within the Spermacoce clade. The unresolved relationships within the species‐rich Spermacoce clade are suggestive of a rapid radiation in which Micrasepalum is one of several phylogenetically recalcitrant lineages, but that can be clearly defined morphologically. The genus is distinctive in having a caducous, 2‐lobed calyx and indehiscent, one‐seeded fruit. An updated identification key for all Caribbean genera of the Spermacoce clade and a full taxonomic revision of Micrasepalum are presented, including descriptions focused on reproductive characters, palynological analysis, a distribution map and new lectotypifications, as well as a new synonym for M. eritrichoides .